"Authorized to work in the US": Examining the myth of porous borders in the era of populism for practicing linguists. (October 2020) - Pandey, Anjali
This paper explores top-down, enacted, institutional pushbacks to supermobility and superdiversity in the under-examined arena of academia using emerging frameworks in political economy and the geography of mobility. Zooming in on the discoursal framings of a recent year of job advertisements on a popular, open-source forum for linguists supplemented with qualitatively and quantitatively sourced data from international, national, and local institutional contexts, the paper examines how macrocontextual pushes toward political populism combined with a synchronous tightening of job markets in academia have enacted a plethora of labels for temporary work in lieu of permanent academic positions—now, increasingly the only option for job seekers in a hypercompetitive academic market. In this manufacturing of euphemization discourse, we witness the invention of novel, microlinguistically rendered lexicalizations of semiotic redundancy in academic capitalism's own obfuscation of profit margins, and a concomitant manufacturing of a new discourse of rationality in which floating semiotic signifiers at multiple scales deploy nationality-criteria to justify ethnic exclusion and/or entry into academic space. More crucially, in these commonsensical framings, we encounter both causation and consequence of newly enacted barriers to transnational mobility. In challenging the myth of porous borders for mobile professionals in the post-global moment, these emerging linguistic signifiers point to the ascendancy of a new public affectivity on display in intellectual spheres and a saturation of sentiment toward illiberality.